Analisis Efisiensi Biaya Persediaan Patchouli Oil (Minyak Nilam) Menggunakan Metode EOQ Dengan Mempertimbangkan Kapasitas Gudang Pada PT XYZ - Puspita, Sesaria Mardhiani Rachma; Alimoeso, Sutarto; Adhaviani, Alfina Marta (Jurnal Sistem Transportasi & Logistik, 2025)
The research at hand addresses a consequential concern related to PT XYZ's procurement procedure, specially their process to order raw materials for the production process in excessive quantities. This practice of them lead to the accretion of raw materials with in the company's warehouse due to limited storage capacity. The focal point of this study is to determine the optimal quantity of ordering raw materials and to indicate the suitable warehouse size that will result in the most cost effective total inventory management. To accomplish this objective, the research adopts well-establishes process EOQ (Economic Order Quantity) model with ll development. Moreover the study considers the significant of warehouse capacity by implementing the Lagrange Multiplier Method. Eventually consequences of the research display that the optimal order quantities for raw material A and B are 55.2 tons and 36.8 tons respectively. Additionally the study indicate that the optimal total inventory cost for raw materials A and B, representing to Rp21,362,417 and Rp17,533,999, respectively.